TARS2 Variants Cause Combination Oxidative Phosphorylation Deficiency-21: A Case Report and Literature Review - Gao, Xin; Xin, Guoyan; Tu, Ya; Liang, Xiaoping; Yang, Huimin; Meng, Hong; Wang, Yumin (Neuropediatrics, 2023)
Objective The aim of the study is to explore the clinical and genetic characteristics of the combined oxidative phosphorylation defect type 21 (COXPD21) caused by the TARS2 compound heterozygous pathogenic variants, and to improve clinicians' awareness of the disease.Methods The proband was a girl of first birth, with repeated refractory hypokalemia, hearing impairment, developmental delay, intellectual disability, developmental retardation after infection, high limb muscle tension, and increased serum lactate as the clinical phenotype. The clinical performance, diagnosis, treatment process, and gene characteristics of COXPD21 caused by TARS2 of the case were analyzed, reviewed, and compared with the literature from the CNKI, Wanfang Data, and biomedical literature database (PubMed) until November 2021.Results The child was diagnosed with COXPD21 after two heterozygous variants in the TARS2 gene were found via whole exome sequencing. One of the variants was c.1679(exon14) A > C (p.Asp560Ala) missense, derived from the mother, and the other was c.1036(exon10)C > T (p.Arg346Cys) missense, derived from the father. The literature was searched and reviewed with the keywords “mitochondrial encephalomyopathy,” “TARS2,” and “combination oxidative phosphorylation deficiency type 21.” A total of four complete domestic and foreign cases were collected from the literature search.Conclusion COXPD21 onset by a complex heterozygous variant of TARS2 causes refractory hypokalemia, which is rarely reported in China and abroad.
Keywords: combination oxidative phosphorylation deficiency-21; TARS2 gene; whole exome sequencing; hypokalemia